2024
DOI: 10.3390/molecules29030596
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Compound, Antioxidant, Antibacterial, and In Silico Studies of Extracts from the Aerial Parts of Lactuca saligna L.

Aziz Bouymajane,
Fouzia Rhazi Filali,
Soumia Moujane
et al.

Abstract: Medicinal plants are considered a major source for discovering novel effective drugs. To our knowledge, no studies have reported the chemical composition and biological activities of Moroccan Lactuca saligna extracts. In this context, this study aims to characterize the polyphenolic compounds distributed in hydro-methanolic extracts of L. saligna and evaluate their antioxidant and antibacterial activities; in addition, in silico analysis based on molecular docking and ADMET was performed to predict the antibac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 59 publications
(60 reference statements)
0
2
0
Order By: Relevance
“…One research group investigated the chemical composition and biological activities of Moroccan Lactuca saligna extracts. These scientists characterized the polyphenolic compounds present in the hydro-methanolic extracts and assessed their antioxidant and antibacterial effects [ 144 ]. A total of 29 phenolic compounds were identified, including dicaffeoyltartaric acid, luteolin 7-glucuronide, 3,5-di-O-caffeoylquinic acid, and 5-caffeoylquinic acid.…”
Section: Recent Studies and Emerging Trends On Polyphenolsmentioning
confidence: 99%
See 1 more Smart Citation
“…One research group investigated the chemical composition and biological activities of Moroccan Lactuca saligna extracts. These scientists characterized the polyphenolic compounds present in the hydro-methanolic extracts and assessed their antioxidant and antibacterial effects [ 144 ]. A total of 29 phenolic compounds were identified, including dicaffeoyltartaric acid, luteolin 7-glucuronide, 3,5-di-O-caffeoylquinic acid, and 5-caffeoylquinic acid.…”
Section: Recent Studies and Emerging Trends On Polyphenolsmentioning
confidence: 99%
“…Computational analyses pointed out that these compounds could function as optimal candidates for the production of groundbreaking antibacterial agents. Further investigations through in vitro and in vivo studies are essential to elucidate the primary biological effects of these plants [ 144 , 145 ]. A literature review compiling diverse polyphenols effective against S. aureus strains indicated that flavonoids were particularly potent against clinical isolates.…”
Section: Recent Studies and Emerging Trends On Polyphenolsmentioning
confidence: 99%